Solder alloy, solder paste, solder ball, preformed solder, solder joint, in-vehicle electronic circuit, ECU electronic circuit, in-vehicle electronic circuit device, and ECU electronic circuit device
Patent Information
- Application Number
- CN202580012907.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-04
- Filing Date
- 2025-02-03
- Publication Date
- 2026-09-01
AI Technical Summary
然而,如上所述,Sn-Ag-Cu软钎料合金在以往未被想到的严苛环境下,会有在接合界面形成的金属间化合物层变厚,且因剪切应力而在电极与软钎料合金的接合界面发生剥离的顾虑
[0022] Solution for solving the problem
Smart Images

Figure CN122680133A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to solder alloys, solder paste, solder balls, preformed solder, brazed joints, automotive electronic circuits, ECU electronic circuits, automotive electronic circuit devices, and ECU electronic circuit devices. Background Technology
[0002] Automobiles are equipped with electronic circuits (hereinafter referred to as "vehicle electronic circuits") that have electronic components soldered onto printed circuit boards. These circuits are used to electrically control the engine, power steering, brakes, and other systems, and are crucial safety components for vehicle operation. In particular, the ECU (Engine Control Unit), which controls the vehicle's electronic circuits to improve fuel efficiency, must be able to operate stably and without failure for extended periods. Due to the expanding applications, these vehicle electronic circuits are installed in locations subjected to various external loads such as temperature differences, impacts, and vibrations.
[0003] For example, automotive electronic circuits located in the engine compartment are exposed to temperatures exceeding 125°C when the engine is running. On the other hand, when the engine is stopped, they are exposed to temperatures as low as -40°C in cold regions. Therefore, automotive electronic circuits used in harsh environments employ highly reliable solder alloys.
[0004] In the past, Sn-Ag-Cu solder alloys have been used as a highly versatile solder alloy. However, as mentioned above, Sn-Ag-Cu solder alloys may experience thickening of the intermetallic compound layer at the bonding interface under previously unforeseen harsh conditions, and there are concerns that shear stress may cause delamination at the bonding interface between the electrode and the solder alloy. Therefore, various explorations have been conducted to find solder alloys that can maintain bonding strength even under harsh operating conditions.
[0005] Patent Document 1 discloses a Sn-Ag-Cu-In-Sb-Co-Ge solder alloy with high thermal cycling resistance, in which the Sn-Ag-Cu solder alloy contains In, Sb, and Co. The same document also explains that this solder alloy, in addition to its thermal cycling resistance, can suppress delamination. To achieve this effect, the same document further describes how, while Bi was previously added to suppress the melting point rise caused by Sb, In was used instead of Bi to improve delamination.
[0006] Patent Document 2 discloses a Sn-Ag-Cu-In-Sb-Ni-Co solder alloy as a solder alloy with high thermal cycling resistance. The same document explains that this solder alloy, in addition to its thermal cycling resistance, can also suppress porosity and delamination. Furthermore, the same document describes how achieving a balance between Sb and In content can improve thermal cycling resistance and suppress delamination and porosity. Additionally, the same document states that, based on the viewpoints of thermal cycling resistance and porosity suppression, it is also possible to include Fe, etc.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent No. 6349615
[0010] Patent Document 2: Japanese Patent No. 6420936 Summary of the Invention
[0011] The problem the invention aims to solve
[0012] As mentioned above, the inventions described in Patent Documents 1 and 2 both include evaluations of heat cycle resistance and delamination. Patent Document 2 further evaluates the occurrence of porosity. Additionally, the melting point is evaluated to suppress the rise in reflow temperature.
[0013] However, these evaluations alone are insufficient for soft solder alloys used in automotive electronic circuits. For example, in automotive electronic circuits, external stresses are applied to the circuits when a car carrying the electronic circuits travels on rough roads. Therefore, exhibiting high shear strength is crucial for brazed joints.
[0014] Furthermore, even if a brazed joint is formed that is difficult to break, it will eventually fracture if stress is continuously applied. This sustained stress is believed to be caused by exposure to environments with drastic temperature differences. This is due to the different coefficients of thermal expansion of the electrodes, the intermetallic compounds formed at the joint interface, and the bulk materials. In particular, even with increased load on the brazed joint, no fracture site becomes the failure mode at the joint interface. Since the joint interface is bonded to the electrodes, it is not easy to alleviate stress at the joint interface. However, physical and electrical loads are primarily applied to the joint interface of the brazed joint. Therefore, it is believed that using a more easily deformable bulk material to alleviate stress can suppress failure.
[0015] However, patent documents 1 and 2 do not address shear strength and failure modes at all, making it difficult to say that they reflect the actual situation in the use of brazed joints. Since brazed joints are used to electrically connect substrates and electronic components, breakage at the joint interface should be avoided as much as possible.
[0016] On the other hand, as mentioned above, the evaluation of the brazed joint under conditions of continuous stress is carried out by thermal cycling tests. In this regard, the inventions described in Patent Documents 1 and 2 have examined thermal cycling resistance. However, in Patent Document 1, the total crack length at 2000 cycles was evaluated using the average value of four samples. Furthermore, Patent Document 2 observed crack occurrence at 3000 cycles using ten samples and also considered evaluating whether cracks occurred across the brazed joint.
[0017] As described in Patent Document 1, when evaluating solely based on average values, there may be samples with shorter total crack lengths and samples with longer total crack lengths. If the average value is lower, the sample will be treated as exhibiting excellent performance. Originally, if a sample with a longer total crack length is included, the issue of thermal cycling resistance as a brazed joint would be overlooked.
[0018] The evaluation described in Patent Document 2 is considered to have a general grasp of cracks that cause complete breakage of brazed joints. However, samples where the brazed joint is almost completely broken are also considered to have excellent performance. If a large number of samples out of 10 show cracks that almost completely break the brazed joint, it must be considered that there is some problem, but such a group of samples is also considered to have excellent performance. Furthermore, although the invention described in Patent Document 2 rarely evaluates cracks at 3000 cycles, when there are concerns that cracks may occur that break the brazed joint at more cycles, it must be considered that there are still issues with heat cycle resistance.
[0019] In particular, for brazed joints installed in automotive electronic circuits, from a safety perspective, it is essential to minimize the risk of breakage. The thermal cycling evaluations in Patent Documents 1 and 2 include the possibility of breakage under extremely short cycles. That is, if there are significant differences in the evaluation results, it may include samples that were considered problem-free but still broke immediately.
[0020] Therefore, patent documents 1 and 2 completely fail to examine shear strength and failure mode, which are important characteristics of brazed joints. Furthermore, with the advancement of automotive electrification in recent years, and given the anticipated continued increase in the number of substrates used, it is urgent to develop soft solder alloys that can guarantee high-probability thermal cycling resistance. In addition, considering the heat resistance of electronic components, it is desirable to exhibit a melting point similar to that of conventional alloys.
[0021] Therefore, the objective of this invention is to provide solder alloys, solder pastes, solder balls, preformed solders, brazed joints, automotive electronic circuits, ECU electronic circuits, automotive electronic circuit devices, and ECU electronic circuit devices that have low melting points, high shear strength, appropriate failure modes, and excellent thermal cycling resistance.
[0022] Solution for solving the problem
[0023] The inventors have re-examined the solder alloys disclosed in Patent Documents 1 and 2. Their conclusion is that the shear strength of the Sn-Ag-Cu-In-Sb-Co-Ge solder alloy of Example 12 in Patent Document 1 and the Sn-Ag-Cu-In-Sb-Ni-Co-Fe solder alloy of Example 15 in Patent Document 2 is similar to that of conventional solder alloys, but there is room for improvement.
[0024] These solder alloys may not have an alloy composition designed to improve shear strength. It should be understood that even if the content of one component varies among different solder alloys, the overall properties will also be different. A combination of alloying elements with a specific content is considered as a whole and technically evaluated.
[0025] Therefore, the inventors conducted a detailed investigation into suppressing the rise in melting point while simultaneously improving shear strength and failure mode. The results showed that adding a specific amount of Fe to Example 12 of Patent Document 1 reduced the melting point by approximately 8-10°C. This is presumably because adding a specific amount of Fe to the Sn-Ag-Cu-In-Sb-Co-Ge solder alloy, due to the synergistic effect with Co, resulted in a finer microstructure of the solder alloy, thus suppressing the precipitation of coarse compounds.
[0026] Furthermore, it was observed that when Fe is added to Sn-Ag-Cu-In-Sb-Co-Ge solder alloys, equivalent melting points, shear strengths, and failure modes are obtained regardless of the presence or absence of Ge. Consequently, it was also observed that Ge can be treated as an arbitrary element in Sn-Ag-Cu-In-Sb-Co-Fe solder alloys.
[0027] In Example 15 of Patent Document 2, a slightly higher melting point was observed. This is presumably because in the Sn-Ag-Cu-In-Sb-Co-Fe solder alloy, if Ni is present, the solid phase of Ni begins to precipitate at a higher temperature during solidification. Furthermore, since the Cu content is low, it is believed that the melting point increases due to a slight deviation from the eutectic composition of Sn-Ag-Cu. Therefore, the observation obtained is that if Ni is removed from Example 15 of Patent Document 2 and the Cu content is increased accordingly by 0.1 to 0.4%, the melting point decreases while the shear strength significantly increases.
[0028] Furthermore, it was observed that when the alloy microstructure contains Co and Fe in a fine-grained manner, the fracture occurs in bulk, thus exhibiting an appropriate failure mode. However, it was also observed that even with adjustments to the Co and Fe contents, excessive Ag and Sb contents can lead to fracture at the interface. This is presumed to be due to the increased bulk strength resulting from compound precipitation, even with excessive Co or Fe contents. Moreover, it was observed that higher Cu content leads to deterioration of shear strength and the failure mode occurring at the interface. This is presumed to be due to hypereutectic formation, resulting in the precipitation of coarse Cu6Sn5 at the interface.
[0029] In addition to the above insights, Patent Documents 1 and 2 demonstrate the ability to exhibit heat cycling resistance. However, the inventors have confirmed that even in the embodiments described in each patent document, some components fracture within extremely short cycles. This indicates a significant difference in evaluation results. Therefore, using conventional evaluation methods, even solder alloys considered to have high heat cycling resistance may contain components with low heat cycling resistance, necessitating a more accurate evaluation. Therefore, the inventors have found that using standard deviation to evaluate the number of fracture cycles in the heat cycling resistance assessment is most effective. By evaluating using standard deviation, solder alloys with low heat cycling resistance that have been previously overlooked can be identified, and heat cycling resistance can be evaluated with greater precision.
[0030] Therefore, the inventors determined the number of fracture cycles using the standard deviation as an evaluation of thermal cycling resistance. As a result, they obtained the following insight: solder alloys with each constituent element within a specific range, in addition to possessing the aforementioned characteristics of low melting point, high shear strength, and appropriate failure mode, also exhibit a standard deviation of fracture cycles below a specific value, thus completing this invention.
[0031] The present invention, which was accomplished based on these insights, is as follows.
[0032] (0) A soft solder alloy, characterized in that, by mass % Ag: 2.0~3.6%, Cu: 0.6~0.9%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: 0.0010~0.0500%, and the balance being Sn.
[0033] (1) A soft solder alloy, characterized in that it has an alloy composition of Ag: 2.0~3.6%, Cu: 0.6~0.9%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: 0.0010~0.0500% by mass, with the balance being Sn.
[0034] (2) The solder alloy as described in (0) or (1) above, wherein the alloy composition (solder alloy) further contains at least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al and Si in a total of 0.100% or less by mass%.
[0035] (3) The solder alloy as described in any of (0) to (2) above, wherein the alloy composition (solder alloy) satisfies the following equations (1) and (2).
[0036]
[0037] In equations (1) and (2) above, Ag, Cu, In, Sb, Fe and Co are the contents of the aforementioned solder alloy in terms of mass%.
[0038] (4) A solder paste having solder powder composed of a solder alloy as described in any one of (0) to (2) above.
[0039] (5) A solder ball composed of a solder alloy as described in any one of (0) to (2) above.
[0040] (6) A preformed solder, which is composed of a solder alloy as described in any one of (0) to (2) above.
[0041] (7) A brazing joint having a soft solder alloy as described in any one of (0) to (2) above.
[0042] (8) An on-board electronic circuit, characterized in that it has a soft solder alloy as described in any one of (0) to (2) above.
[0043] (9) An ECU electronic circuit, characterized in that it has a solder alloy as described in any one of (0) to (2) above.
[0044] (10) An in-vehicle electronic circuit device, characterized in that it comprises an in-vehicle electronic circuit as described in (8) above.
[0045] (11) An ECU electronic circuit device, characterized in that it comprises an ECU electronic circuit as described in (9) above. Attached Figure Description
[0046] Figure 1 This shows an optical microscope image of the sample after the shear strength was measured. Figure 1 (a) is Example 4. Figure 1 (b) is Comparative Example 19. Figure 1 (c) is Comparative Example 3. Detailed Implementation
[0047] The present invention will be described in more detail below. In this specification, unless otherwise stated, "%" in relation to the composition of the solder alloy means "mass %".
[0048] 1. Soft solder alloy
[0049] (1) Ag: 2.0~3.6%
[0050] Ag contributes to improved shear strength, appropriate failure modes due to Ag3Sn precipitation, lower melting point, and improved thermal cycling resistance. When the Ag content is less than 2.0%, the amount of compound precipitation is low, resulting in reduced shear strength. The lower limit of Ag content is 2.0% or more, preferably 2.5% or more, more preferably 2.7% or more, and even more preferably 3.0% or more.
[0051] On the other hand, when the Ag content exceeds 3.6%, it becomes hypereutectic, leading to the precipitation of a large amount of Ag3Sn, which increases the strength of the bulk and makes the interface the failure mode. Additionally, it can sometimes reduce shear strength and raise the melting point due to the large amount of compound precipitation. Furthermore, due to the increased bulk strength, cracks occur during thermal cycling tests, the standard deviation increases, and thermal cycling resistance is poor. The upper limit for Ag content is 3.6% or less, preferably 3.4% or less, and more preferably 3.2% or less.
[0052] (2) Cu: 0.6~0.9%
[0053] Cu helps improve shear strength, appropriately modulates the failure mode by controlling the formation of intermetallic compounds at the interface, lowers the melting point, and improves thermal cycling resistance. Furthermore, if the content is appropriate, it can suppress the precipitation of coarse Cu6Sn5. When the Cu content is less than 0.6%, Cu6Sn5 is not fully precipitated, resulting in poor shear strength. Additionally, the melting point increases. The lower limit for Cu content is 0.6% or more, preferably 0.7% or more.
[0054] On the other hand, when the Cu content exceeds 0.9%, it becomes hypereutectic, resulting in the precipitation of coarse Cu6Sn5 at the bonding interface, thus deteriorating the shear strength. Furthermore, the failure mode becomes the bonding interface. In addition, due to the deterioration of shear strength, cracks occur during thermal cycling tests, the standard deviation increases, and thermal cycling resistance is poor. The upper limit for the Cu content is 0.9% or less, preferably 0.8% or less.
[0055] (3) In: 1.0~5.0%
[0056] In contributes to improved shear strength, appropriate failure mode, and improved thermal cycling resistance. When the In content is less than 1.0%, the shear strength is poor, and due to reduced wettability, wetting spread is insufficient. Furthermore, the failure mode is inappropriate due to insufficient solid solution strengthening, and thermal cycling resistance is also poor. The lower limit of the In content is 1.0% or more, preferably 1.5% or more, more preferably 2.0% or more, further preferably 2.5% or more, and particularly preferably 3.0% or more.
[0057] On the other hand, when the In content exceeds 5.0%, the melting point rises due to the large amount of compound precipitation. Furthermore, the bulk strength is excessively increased, while the shear strength decreases. There are also concerns about damage at joint interfaces or parts. Additionally, due to the increased bulk strength, cracks occur during thermal cycling tests, the standard deviation value increases, and thermal cycling resistance is poor. The upper limit for the In content is 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, and even more preferably 3.5% or less.
[0058] (4) Sb: 3.0~5.0%
[0059] Sb helps to suppress melting point rise, improve shear strength, optimize failure mode, and improve thermal cycling resistance. When the Sb content is less than 3.0%, the shear strength is poor due to insufficient solid solution strengthening of Sn and precipitation strengthening of Sn-Sb compounds. The lower limit of Sb content is 3.0% or more, preferably 3.5% or more, more preferably 3.6% or more, further preferably 3.8% or more, particularly preferably 3.9% or more, and most preferably 4.0% or more.
[0060] On the other hand, when the Sb content exceeds 5.0%, the shear strength is poor due to the formation of coarse SnSb compounds. Furthermore, wettability deteriorates, and the failure mode becomes interface or component failure, which is undesirable. Moreover, due to the increased bulk strength, cracks occur during thermal cycling tests, the standard deviation becomes larger, and thermal cycling resistance is poor. The upper limit of the Sb content is 5.0% or less, preferably 4.8% or less, more preferably 4.6% or less, further preferably 4.5% or less, particularly preferably 4.3% or less, and most preferably 4.1% or less.
[0061] (5) Fe: 0.0010~0.0300%
[0062] Fe contributes to improved shear strength, appropriate failure modes, and enhanced thermal cycling resistance. When the Fe content is less than 0.0010%, the interfacial strengthening effect due to the modification of the intermetallic compound layer formed at the interface is insufficient, resulting in poor shear strength. The lower limit of the Fe content is 0.0010% or more, preferably 0.0050% or more, more preferably 0.0100% or more, further preferably 0.0150% or more, and particularly preferably 0.0200% or more.
[0063] On the other hand, when the Fe content exceeds 0.0300%, the bulk strength is excessively increased due to the precipitation of Sn-Fe compounds, resulting in poor shear strength and concerns about damage at the bonding interface. The upper limit of the Fe content is 0.0300% or less, preferably 0.0270% or less, and more preferably 0.0250% or less.
[0064] (6) Co: 0.0010~0.0500%
[0065] Co helps to suppress melting point rise, improve shear strength, optimize failure mode, and improve thermal cycling resistance. When the Co content is less than 0.0010%, the shear strength decreases due to insufficient micronization of the bulk material. The lower limit of the Co content is 0.0010% or more, preferably 0.0030% or more, more preferably 0.0060% or more, and even more preferably 0.0080% or more.
[0066] On the other hand, when the Co content exceeds 0.0500%, the bulk strength increases due to the precipitation of Sn and Co compounds, thus the failure mode becomes the interface. Furthermore, the melting point rises significantly due to the large amount of compound precipitation, and wettability deteriorates, resulting in a decrease in shear strength. In addition, the increased bulk strength leads to cracking during thermal cycling tests, a larger standard deviation, and poor thermal cycling resistance. The upper limit for the Co content is 0.0500% or less, preferably 0.0300% or less, and more preferably 0.0100% or less.
[0067] (7) Balance: Sn
[0068] The balance of the solder alloy of the present invention is Sn. In addition to the aforementioned elements, unavoidable impurities may also be present. The presence of unavoidable impurities does not affect the aforementioned effects. Furthermore, in the Sn-Ag-Cu-In-Sb-Fe-Co solder alloy of the present invention, when the contents are within the above-mentioned ranges, the melting point of Ni increases sharply even with a small amount added, so it is preferable to exclude it. Moreover, in the present invention, Mn increases the melting point, deteriorates wettability, prevents the formation of suitable compounds, and reduces shear strength, so it is preferable to exclude it. Furthermore, when Bi and In coexist, a low-melting-point Sn-In-Bi phase is formed. Given creep deformation, since the low-melting-point phase has a low melting point that makes room temperature feel like a high-temperature environment, it is prone to creep deformation, leading to a decrease in strength. Therefore, in the present invention, it is preferable to exclude Bi.
[0069] (8) At least one of the following: Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al, and Si, totaling less than 0.100%.
[0070] The solder alloy of the present invention, without impairing the effects of the present invention, may contain at least one of the following elements as arbitrary elements in a total concentration of less than 0.100%: Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al, and Si. Preferably, the total concentration is 0.080% or less. The lower limit of the content is not particularly limited, but it can be 0.0001% or more.
[0071] Equations (9)(1) and (2)
[0072]
[0073] In equations (1) and (2) above, Ag, Cu, In, Sb, Fe and Co are the contents of the solder alloy in terms of mass%.
[0074] Formula (1) is a formula that takes into account the balance of additive elements in the solder alloy of the present invention. The solder alloy of the present invention can achieve low melting point, high shear strength, appropriate failure mode and high thermal cycling resistance through the synergistic effect of each constituent element. Therefore, if the balance of all constituent elements other than Sn is optimized, all the effects of the present invention can be further improved. In formula (1), the contents of Ag, Cu, In and Sb are about 10 to 100 times that of Fe and Co. However, it is considered that their contribution to the solder alloy is the same. Therefore, in the present invention, in order to further improve low melting point, high shear strength, appropriate failure mode and high thermal cycling resistance with a single composition, it is preferable to set a balanced content.
[0075] Equation (2) is a formula that takes into account the balance between In and other elements in the solder alloy of the present invention. Compared with other additive elements, the content range of In, whether below the lower limit or above the upper limit, will result in poor shear strength and an inappropriate failure mode. This is a phenomenon unique to the Sn-Ag-Cu-In-Sb-Co-Fe solder alloy of the present invention. The reason for this is not yet clear, but it can be speculated that it is due to insufficient wettability leading to insufficient wetting spread, and insufficient solid solution strengthening effect.
[0076] In the calculations of equations (1) and (2), the measured values of the alloy composition shown in Tables 1 and 2 below are used, and the values described in the tables are used. That is, in the calculations of equations (1) and (2), for the measured values shown in Tables 1 and 2 below, all digits less than the significant figures are treated as 0. For example, when the measured value of Co content is “0.008” mass%, the Co content used to calculate equations (1) and (2) is not in the range of 0.0075~0.0084%, but is treated as “0.008000…”. In equation (1), the fifth decimal place is rounded to the fourth decimal place. In equation (2), the first decimal place is rounded to the nearest whole number.
[0077] In addition, when calculating equations (1) and (2) from the alloy composition specifically disclosed in the patent documents and other documents described in this specification, the same method shall be used.
[0078] As mentioned above, in an alloy, not all constituent elements function individually, but rather all constituent elements as a whole constitute a single entity. Therefore, it is rare for a single element to simultaneously exhibit all the superior effects. Thus, as stated above, in order to exhibit superior properties within the optimal content range of each constituent element, it is necessary to review the constituent elements as a whole. In the solder alloy of the present invention, in order to achieve all of the following at a high level with a single composition: low melting point, high shear strength, appropriate failure mode, and high thermal cycling resistance, it is preferable to satisfy equations (1) and (2).
[0079] The lower limit of formula (1) is preferably 0.0020 or more, more preferably 0.0021 or more, even more preferably 0.0022 or more, even more preferably 0.0023 or more, particularly preferably 0.0024 or more, and most preferably 0.0028 or more, 0.0029 or more, 0.0033 or more, 0.0034 or more, 0.0035 or more, 0.0036 or more, 0.0038 or more, 0.0042 or more, 0.0043 or more, 0.0045 or more, 0.0046 or more, 0.0048 or more, 0.0049 or more, 0.0050 or more, and 0.0057 or more. (1) The upper limit of the formula is preferably 0.0090 or less, more preferably 0.0086 or less, even more preferably 0.085 or less, even more preferably 0.0083 or less, particularly preferably 0.0076 or less, and most preferably 0.0073 or less, 0.0071 or less, 0.0069 or less, 0.0068 or less, 0.0067 or less, 0.0066 or less, 0.0065 or less, 0.0064 or less, 0.0061 or less, and 0.0060 or less.
[0080] (2) The lower limit is preferably 445 or more, more preferably 525 or more, even more preferably 630 or more, even more preferably 700 or more, particularly preferably 787 or more, and most preferably 788 or more, 840 or more, 1050 or more, 1225 or more, 1260 or more, 1261 or more, 1313 or more, 1378 or more, 1379 or more, 1400 or more, 1401 or more, 1470 or more, 1471 or more, and 1488 or more. (2) The upper limit of the formula is preferably 3560 or less, more preferably 3501 or less, even more preferably 3151 or less, even more preferably 2801 or less, particularly preferably 2679 or less, and most preferably 2678 or less, 2626 or less, 2450 or less, 2451 or less, 2363 or less, 2143 or less, 2142 or less, 2101 or less, 2100 or less, 1970 or less, 1969 or less, 1891 or less, 1890 or less, 1838 or less, 1786 or less, 1785 or less, 1751 or less, 1750 or less, 1681 or less, 1680 or less, 1576 or less, and 1575 or less.
[0081] Furthermore, in the embodiments described later, a determination result of "◎" indicates that it is practically more preferred than "〇". Since "〇" is a better result than the past, it falls within the scope of the present invention and is treated as an example if other evaluation results are also excellent. Since "×" is a insufficient result in the present invention, it is outside the scope of the present invention and is treated as a comparative example.
[0082] The thermal cycling resistance of this invention takes into account the deviation of each sample after thermal cycling tests; the smaller the deviation from the average value, the higher the evaluation. Therefore, evaluations that compare only the average value, as discussed in the past, are significantly different in their significance.
[0083] 2. Solder paste
[0084] The solder paste of the present invention is a mixture of solder powder composed of the above-mentioned alloy composition and flux. The flux used in the present invention is not particularly limited as long as it can be soldered by common methods. Therefore, any flux appropriately mixed with commonly used rosin, organic acids, activators, thixotropic agents, and solvents is acceptable. The mixing ratio of the metal powder component and the flux component in the present invention is not particularly limited, but preferably the metal powder component is 70-90% by mass, and the flux component is 10-30% by mass.
[0085] 3. Solder ball
[0086] The solder alloy of the present invention can be used as solder balls. When used as solder balls, the solder alloy of the present invention can be manufactured using a drop-down method, a common method in the art. Alternatively, brazed joints can be manufactured by processing using common methods in the art, such as mounting a solder ball onto an electrode coated with flux and joining them. The particle size of the solder balls is preferably 1 μm or more, more preferably 10 μm or more, further preferably 20 μm or more, and particularly preferably 30 μm or more. The upper limit of the particle size of the solder balls is preferably 3000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, and particularly preferably 600 μm or less.
[0087] 4. Pre-formed soft solder
[0088] The solder alloy of the present invention can be used as a preform. Examples of preform shapes include washers, rings, granules, disks, strips, and wires.
[0089] 5. Brazed joints
[0090] The brazing joint of the present invention is suitable for connecting at least two or more components. The term "components to be joined" is not particularly limited as long as they are semiconductors, power modules, inverter products, etc., that use the soft solder alloy of the present invention for electrical connection, such as components, substrates, electronic parts, printed circuit boards, insulating substrates, heat sinks, lead frames, electrode terminals, etc.
[0091] The joining method using the solder alloy of the present invention can be performed according to common methods, such as reflow soldering. The melting temperature of the solder alloy during reflow soldering should preferably be about 20°C higher than the liquidus temperature. Furthermore, when joining using the solder alloy of the present invention, the alloy microstructure can be further refined by considering the cooling rate during solidification. For example, the brazed joint can be cooled at a cooling rate of 2-3°C / s or higher. These other joining conditions can be appropriately adjusted according to the alloy composition of the solder alloy.
[0092] 6. Vehicle electronic circuits, ECU electronic circuits, vehicle electronic circuit devices, ECU electronic circuit devices
[0093] As can be understood from the description to date, the solder alloy of the present invention suppresses melting point rise, exhibits excellent shear strength, appropriate failure mode, and excellent thermal cycling resistance. Therefore, even when used in automotive applications exposed to harsh environments, i.e., vehicle-mounted applications, it can consistently suppress solder joint breakage. Therefore, due to these particularly significant characteristics, the solder alloy of the present invention is especially suitable for soldering electronic circuits mounted in automobiles.
[0094] The term "excellent thermal cycling resistance" in this specification, as illustrated in the examples described later, refers to a standard deviation of less than 1000 cycles until the resistance of the brazed joint increases by 20% after undergoing thermal cycling tests at -40°C and +125°C for 10 minutes each. This characteristic means that even under extremely harsh conditions such as the aforementioned thermal cycling test, the possibility of breakage of the vehicle's electronic circuitry is greatly reduced, and no unusability or malfunction is caused.
[0095] Therefore, the solder alloy of the present invention is more specifically used for soldering automotive electronic circuits or for soldering ECU electronic circuits, and exhibits excellent thermal cycling resistance.
[0096] An "electronic circuit" is a system that uses electronic engineering to combine multiple electronic components, each with its own function, to perform a target function as a whole.
[0097] Examples of electronic components that constitute such electronic circuits include chip resistors, multi-gang resistors, QFPs, QFNs, power transistors, diodes, and capacitors. An electronic circuit assembled from these electronic components is mounted on a substrate, thus forming an electronic circuit device.
[0098] In this invention, the substrate constituting such an electronic circuit device, such as a printed circuit board, is not particularly limited. Its material is also not particularly limited, but heat-resistant plastic substrates (e.g., FR-4 with high Tg and low CTE) can be used as examples. The printed circuit board is preferably a printed circuit board whose Cu pad surface is treated with an organic compound such as an amine or imidazole (OSP: Organic Surface Protection).
[0099] 7. Other
[0100] The solder alloy of the present invention can be manufactured with low alpha radiation by using low alpha radiation materials as its raw materials. This low alpha radiation alloy can suppress soft errors when used for forming solder bumps around memory chips.
[0101] Example
[0102] Although the present invention is illustrated by the following embodiments, the present invention is not limited to the following embodiments.
[0103] To demonstrate the effectiveness of the present invention, the soft solder alloys described in Tables 1 and 2 were used to evaluate (1) melting point, (2) shear strength, (3) failure mode, and (4) thermal cycling test (TCT). Furthermore, regarding (4), Example 4 and Comparative Example 19 were selected from the following examples and comparative examples, and their evaluation results are shown.
[0104] (1) Melting point
[0105] For the solder alloys shown in Tables 1 and 2, the temperatures were determined from the DSC curves. The DSC curves were obtained using a Seiko Instruments DSC (model: 6200) at atmospheric temperature with a heating rate of 5°C / min. The liquidus temperature was determined from the obtained DSC curves and set as the melting point. When the melting point is below 232°C, reflow soldering can be performed at the same temperature as before. When the melting point is above 232°C, reflow soldering cannot be performed as before due to the high melting point.
[0106] (2) Shear strength
[0107] (2-1) Sample preparation
[0108] The solder alloys shown in Tables 1 and 2 were cast to produce solder sheets (diameter: 1 mm, thickness: 0.15 mm). Chip resistors were soldered to the Cu-OSP electrodes of the FR-4 substrate using a reflow oven (SNR-615: manufactured by Senju Metal Industries, Ltd.). The chip resistors used were 3216CR (CR32-114JV: manufactured by Hokuriku Electric Industries, Ltd.). The reflow profile was set at 220°C or higher for 40 seconds, with a peak temperature of 245°C in a nitrogen atmosphere.
[0109] (2-2) Evaluation of shear strength
[0110] For samples prepared in this manner, a shear testing machine (STR-1000: manufactured by RHESCA) was used with a shear rate set to 6 mm / min to determine the shear strength. A shear strength of 84.0 N or higher was rated "◎". A shear strength of 70.0 N or higher but less than 84.0 N was rated "〇". A shear strength less than 70.0 N was rated "×".
[0111] (3) Destruction Mode
[0112] The failure modes of the samples evaluated in "(2) Shear Strength" were observed using an optical microscope (VHX-5000: KEYENCE). Samples that failed as bulk were rated "◎". Samples that failed as bulk and as intermetallic compounds (IMC) at the interface were rated "〇". Samples that failed as intermetallic compounds at the interface were rated "×".
[0113] (4) Thermal Cycling Test (TCT)
[0114] Example 4 was selected from Table 1, and Comparative Example 19 was selected from Table 2. Each solder alloy was atomized to form solder powder. This powder was then mixed with a soldering flux (GLV, manufactured by Senju Metal Industries, Ltd.) consisting of rosin, solvent, activator, thixotropic agent, and organic acid to prepare solder paste for each solder alloy. The solder paste contained 88% by mass of alloy powder and 12% by mass of flux. The solder paste was printed onto a 0.8mm thick printed circuit board (material: FR-4) using a 100μm thick metal mask. 12mm × 12mm LGA (Grid Array Package) components were then mounted using a pick-and-place machine, and reflow soldering was performed using the same reflow profile as described in "(2)(2-1)" above. Fifteen samples were prepared for Example 4, and fourteen samples were prepared for Comparative Example 18.
[0115] The prepared samples were placed in a thermal cycling test apparatus (TSA-101L-A, manufactured by ESPEC) with conditions set at a low temperature of -40°C, a high temperature of +125°C, and a holding time of 10 minutes. Resistance values were measured during the test. For samples that fractured when the initial resistance value increased by 20%, the average number of fracture cycles and the standard deviation were calculated. A standard deviation below 1000 was considered practically acceptable. Conversely, a standard deviation exceeding 1000 was considered unsuitable for practical use because some samples deviated significantly from the average.
[0116] The evaluation results of (1) to (3) above are shown in Table 1 and Table 2. And the evaluation results of (4) are shown in Table 3.
[0117] [Table 1]
[0118]
[0119] [Table 2]
[0120]
[0121] [Table 3]
[0122]
[0123] As shown in Tables 1 and 2, in Examples 1-62, since the content of each constituent element was appropriate, all evaluations were practically tolerable. Furthermore, it can be seen that Examples 1-8, 10-17, 19-24, 27-31, 38, 39, 42, 43, and 46-62, which satisfy equations (1) and (2), showed extremely excellent results in all evaluations. This result indicates that even among practically tolerable results, there are some significantly different and superior examples.
[0124] On the other hand, as shown in Table 2, Comparative Example 1, lacking In, Sb, Fe, and Co, exhibited poor shear strength and an inappropriate failure mode. Comparative Example 2, with its low Ag content, also showed poor shear strength. Comparative Examples 3 and 4, with their high Ag content, also exhibited poor shear strength and inappropriate failure modes.
[0125] Comparative Examples 5 and 6 exhibited poor shear strength due to their low Cu content. In particular, Comparative Example 6, containing Ni, also exhibited an inappropriate failure mode. Comparative Example 7, with its high Cu content, also suffered from poor shear strength and an inappropriate failure mode.
[0126] Comparative Examples 8 and 9 exhibited poor shear strength and inappropriate failure modes due to inappropriate In content. Comparative Example 10 showed poor shear strength due to low Sb content. Comparative Example 11 also showed poor shear strength and inappropriate failure mode due to high Sb content.
[0127] Comparative Examples 12-14 exhibited poor shear strength due to their low Fe content. Comparative Example 15, with its high Fe content, also showed poor shear strength and an inappropriate failure mode.
[0128] Comparative Example 16 has poor shear strength due to its low Co content. Comparative Example 17 has poor shear strength and an inappropriate failure mode due to its high Co content.
[0129] Comparative Examples 18 and 20, each containing Ni or Mn, exhibited significantly increased melting points, poor shear strength, and inappropriate failure modes. Comparative Example 19, containing Bi, also exhibited poor shear strength.
[0130] Furthermore, as can be seen from Table 3, the average number of cycles in Example 4 differs from that in Comparative Example 19 by approximately 300 cycles. However, the standard deviation of the number of cycles in Example 4 is less than 1000, while the standard deviation of the number of cycles in Comparative Example 19 is significantly greater than 1000.
[0131] Therefore, in Example 4, only samples with small deviations and small differences from the average value in the thermal cycling test were observed. It was found that other examples also showed the same results. On the other hand, it was found that in Comparative Example 19, there were samples with large deviations and extremely large differences from the average value in the thermal cycling test.
[0132] Figure 1 This shows an optical microscope image of the sample after the shear strength was measured. Figure 1 (a) is Example 4. Figure 1 (b) is Comparative Example 19. Figure 1 (c) is Comparative Example 3. For example, from... Figure 1It is understood that in Example 4, the brazed joint fractured due to bulk material failure. On the other hand, it is understood that in Comparative Example 19, the brazed joint fractured due to both bulk material failure and the destruction of the intermetallic compound at the joint interface. Furthermore, it is understood that in Comparative Example 3, the brazed joint fractured due to the intermetallic compound at the joint interface. Therefore, it can be concluded that the failure mode in Example 4 is appropriate. The result is similar in other examples.
[0133] Industrial availability
[0134] The solder of the present invention can be used in vehicle electronic circuits such as ECUs, which are electronic circuits controlled by computers to improve fuel efficiency, but it can also be used in consumer electronic devices such as personal computers and achieve excellent results.
Claims
1. A soft solder alloy, characterized in that, An alloy having, by mass%, Ag: 2.0~3.6%, Cu: 0.6~0.9%, In: 1.0~5.0%, Sb: 3.0~5.0%, Fe: 0.0010~0.0300%, Co: 0.0010~0.0500%, with the balance being Sn, wherein the alloy composition satisfies the following equations (1) and (2). In equations (1) and (2), Ag, Cu, In, Sb, Fe and Co are the contents of the solder alloy by mass%.
2. The solder alloy according to claim 1, wherein, The alloy composition further contains at least one of Zr, Ge, Ga, P, As, Pb, Zn, Mg, Cr, Ti, Mo, Pt, Pd, Au, Al and Si, in a total of less than 0.100% by mass.
3. A solder paste having a solder powder composed of a solder alloy as described in claim 1 or 2.
4. A solder ball comprising the solder alloy of claim 1 or 2.
5. A preformed solder, comprising the solder alloy of claim 1 or 2.
6. A brazing joint having the soft solder alloy as described in claim 1 or 2.
7. A vehicle-mounted electronic circuit, characterized in that, It has the soft solder alloy as described in claim 1 or 2.
8. An ECU electronic circuit, characterized in that, It has the solder alloy as described in claim 1 or 2.
9. A vehicle-mounted electronic circuit device, characterized in that, It possesses the vehicle-mounted electronic circuit as described in claim 7.
10. An ECU electronic circuit device, characterized in that, It has the ECU electronic circuit as described in claim 8.
Citation Information
Patent Citations
Intermixing type atomizer
JP1988049615A
Method and device for fitting o-ring
JP1989020936A